Answer:
The sum of one-half and a number is more than eighteen.
The sum of one-half and a number is greater than eighteen.
The sum of one-half and a number is above eighteen.
Step-by-step explanation:
https://brainly.com/question/12165044
Question: Which phrases can be used to represent the inequality? Check all that apply.
One-half + k greater-than 18
Answer:
a. The sum of one-half and a number is more than eighteen. b. The sum of one-half and a number is greater than eighteen.
c. The sum of one-half and a number is above eighteen.
14 Orange-U-happy is an orange-scenteldeaning produthal is manu- factured in disposable doth pads. Each box of 100 pads sonts $5 to man. ufacture. The fixed costs for Orange-1-Hapoy a $30,000. The research development group of the company has determined the demand func- tion to her = 5000 - 20.060, where p is the price for each box a. Write the expense cuation in terms of the demand, b. Expres the expense function in terms of the price 9 c. Write the revenue function in terms of price. p.
Answer:
Consider the following statements, Each box of 100 pads of an orange-u happy costs$5 to manufacturer. The variable costs for manufacturing q boxes at 100 pads will be V=5.4
Step-by-step explanation:
One zero of the polynomial function f(x) = x3 − x2 − 12x is x = 0. What are the zeros of the polynomial function?
Step-by-step explanation:
\Given :
x^{3} +x^{2} -20x
Solution:
x^{3} +x^{2} -20x
taking x common from the given polynomial
⇒x(x^{2} +x-20)=0
⇒x(x(x+5)-4(x+5))=0
⇒x(x+5)(x-4)=0
⇒ x=0 , x+5=0 , x-4=0
⇒x = 0 , x = -5 , x = 4
Answer:
0, x = 4, and x = -3.
Step-by-step explanation:
he zeros of the polynomial function f(x) = x3 − x2 − 12x are x = 0, x = 4, and x = -3. To find these, we can factor the polynomial and set each factor equal to zero. Since x = 0 is already given as a zero, we can factor out x from the polynomial to get f(x) = x(x^2 - x - 12) = x(x - 4)(x + 3) = 0. Thus, the other zeros are x = 4 and x = -3.
I WILL GIVE 20 POINTS TO THOSE WHO ANSWER THIS QUESTION RIGHT NOOOO SCAMS AND EXPLAIN WHY THAT IS THE ANSWER. Find the value of the variable in the figure. The diagram is not a scale.
Volume=30pi
X=___
Answer:
3
Step-by-step explanation:
Volume of a cone
V = pi x r^2 x h/3
So plug in the values we have
30pi = pi x r^2 x 10/3
30 = r^2 10/3
9 = r^2
3 = r
Segment AB has point A located at (4,2). If the distance from A to B is 3 units, which of the following could be used to calculate the coordinates for point B?
3 = √(x - 2)²+(y - 4)^2
3= V(x-4)2 +(y-2)^2
3 = V(x + 2)2 + (y+4)^2
3=(x+4)^2+(y+2)^2
The equation to calculate the coordinates of point B is (b) 3 = √(x - 4)²+(y - 2)²
How to determine the equation?The given parameters are:
A = (4,2)
AB = 3
The distance formula is:
AB = √(x - x1)²+(y - y1)²
So, we have:
3 = √(x - 4)²+(y - 2)²
Hence, the equation to calculate the coordinates of point B is (b) 3 = √(x - 4)²+(y - 2)²
Read more about distance coordinates at:
https://brainly.com/question/7243416
#SPJ1
Peter brought chocolate and vanilla cupcakes to school for his birthday. 2 students picked a vanilla cupcake and 23 students picked a chocolate cupcake. What percentage of the students picked a vanilla cupcake?
Answer:
8%
Step-by-step explanation:
Add 2 and 23 together to get 25.
Divide 2 by 25 to get 0.08.
Covert 0.08 into percentage: 8%
Which equation is y = –6x2 + 3x + 2 rewritten in vertex form?
y = negative 6 (x minus 1) squared + 8
y = negative 6 (x + one-fourth) squared + thirteen-eighths
y = negative 6 (x minus one-fourth) squared + nineteen-eighths
y = negative 6 (x minus one-half) squared + seven-halves
Answer:
Step-by-step explanation:
y = negative 6 (x minus one-fourth) squared + nineteen-eighths
Step-by-step explanation:
y = –6x^2 + 3x + 2
Divide the first 2 terms of the right side by -6:
y = -6(x^2 - 1/2x) + 2
Now complete the square on the expression in the brackets:
y = -6[(x - 1/4)^2 - 1/16] + 2
y = -6(x - 1/4)^2 + 6/16 + 2
y = -6(x - 1/4)^2 + 38/16
y = -6(x - 1/4)^2 + 19/8
Answer: C
Step-by-step explanation:
Maya invests $6,000 into an ETF which earns 3% per year. In 30 years, how much will Maya's investment be worth if interestis compounded semiannually (twice a year)?
Write an equation for a line that passes
through the point (0, 4) and (1,6).
Answer:
y=2x+4
Step-by-step explanation:
PLEASE 100 POINTS AND BRAINLIEST IF U DO IT ALL PLSSSSS I NEED HELP!!!PLSSSSSS HELP PLSSSSS
Applying the volume of a rectangular prism, the following are determined:
A & G has a solution of 120.
B & F: 714
C & E: 56
D & H: 9.5
What is the Volume of a Triangular Prism?Volume = base area × height of prism = 1/2(bh) × H
A. Volume = 1/2(bh) × H = 1/2(6)(8) × 5 = 120 units³
B. Volume = 1/2(bh) × H = 1/2(6)(14) × 17 = 714 units³
C. Volume = 1/2(bh) × H = 1/2(12)(8) × x = 2,688 units³
48x = 2,688
x = 2,688/48
x = 56 units (height of the prism)
D. Volume = base area × height of prism
Plug in the given values
27.36 = base area × 2.88
27.36/2.88 = area of triangular base
area of triangular base = 9.5 units².
E. Volume = 1/2(bh) × H = 1/2(8)(15) × x = 3,360 units³
60x = 3,360
x = 3,360/60
x = 56 units (height of the prism)
F. Volume = 1/2(bh) × H = 1/2(17)(4) × 21 = 714 units³
G. Volume = 1/2(bh) × H = 1/2(3)(5) × 16 = 120 units³
H. Volume = 1/2(bh) × H = 1/2(1.9)(2) × 5 = 9.5 units³
Learn more about volume of triangular prism on:
https://brainly.com/question/21173224
#SPJ1
Hello, can someone help me with this please, I have to watch the video and then answer the questions below.
1. How can having children act out number operations stories help their conceptual understanding?
2. What are your thoughts about the way these teachers put the emphasis on helping children see change in terms of more or fewer/less rather than having them count on to find the exact total?
3. Several of the children in the video are English Language Learners; what evidence do you see that they understand the Big Ideas though they don't articulate them in words?
Seven decreased by four times a number what is the answer
Answer:
7-4g
Step-by-step explanation:
let the number =g
four times the number = 4×g = 4g
seven decreased br four times the number= 7- 4g
therefore, the answer = 7-4g
Jaya has a piece of paper that is 16 inches long and 9 inches wide. She cuts it into pieces that are each 3 inches long and 2 inches wide What is the greatest number of 3-inch-by-2-inch pieces that Jaya can get? Enter the answer in the box.
Answer:
24
Step-by-step explanation:
Jayla has a couple of options for cutting her original piece of paper.
she can cut the 3 inch length from the long dimension of the paper, giving her 5 strips from the length and 4 strips from the width for a total of 20 3×2 piecesshe can cut the 3 inch length from the short dimension of the paper, giving her 3 strips from the 9-inch width, and 8 strips from the 16-inch length, for a total of 3×8 = 24 pieces.The greatest number of 3×2 pieces Jayla can cut is 24.
__
The attachments show the different cuts as described above.
Given that y is inversely proportional to x y =0.25 when x =4, find the value of y when x =5
Answer: y=0.2
Step-by-step explanation:
y∝(1/x)
this implies that
y=k/x eq(*)
when y =0.25 when x =4
0.25=k/4
k=1
for y when x=5
y=k/x
y=1/5
y=0.2
Can anyone help me solve this problem?
Given
[tex] \text{Base = 4} \\ \text{Perpendicular= 8}[/tex]
To Find
Hypotenuse of the triangle.
Assuming,
[tex] \text{Perpendicular = ‘a’}[/tex]
[tex] \text{Base = ‘b’}[/tex]
[tex] \text{Hypotenuse= ‘c’}[/tex]
Solution[tex] \text{(c)² = (a)² + (b)²} \\ \\ \implies \text{ (c)² = (8)² + (4)²} \\ \\ \implies \text{(c)}^{2} = 64 + 16 \\ \\ \implies \text{(c)}^{2} = 80 \\ \\ \implies \text{(c)} = \sqrt{80} \\ \\ \implies\text{(c)} = 8.94[/tex]
[tex]\text{Rounding it to the nearest tenth = 8.9}[/tex]
[tex]\therefore \text{Hypotenuse of the triangle = 8.9}[/tex]
Option D= 8.9 units is the correct answer
Hope this helps!!Prove all the relation of quadric polynomial.
Kindly need help!!!
[tex]{\large{\textsf{\textbf{\underline{\underline{Solution :}}}}}}[/tex]
Let [tex]\alpha[/tex] and [tex]\beta[/tex] be the two zeroes of P(x) = [tex]\sf {a}^{2} + bx + c[/tex]
• A polynomial is always equal to it's factors, also the constant "k" is not equal to zero
[tex] \tt \sf {a}^{2} + bx + c = k(x - \alpha )(x - \beta )[/tex]
• Using distributive property
[tex]\tt \sf {a}^{2} + bx + c = k \bigg( {x}^{2} - \beta x - \alpha x + \alpha \beta \bigg)[/tex]
[tex]\tt \sf {a}^{2} + bx + c = k {x}^{2} -k (\beta x )- k(\alpha x )+k( \alpha \beta )[/tex]
• Taking common
[tex]\tt \sf {a}^{2} + bx + c = k {x}^{2} -kx (\beta + \alpha)+k( \alpha \beta ) - - (1)[/tex]
• Equating coefficients of like terms
[tex] \sf \: a = k - - (2)[/tex]
[tex] \sf b = - k( \alpha + \beta ) - - (3)[/tex]
[tex] \sf c = k \alpha \beta - - (4)[/tex]
★ From 3
[tex] \sf b = - k( \alpha + \beta ) - - (3)[/tex]
★ From 2 we have a = k so we have -
[tex] \sf b = - a( \alpha + \beta ) [/tex]
[tex]\sf - \dfrac{b}{a} = ( \alpha + \beta ) [/tex]
[tex]\sf \therefore \boxed {{ \red{( \alpha + \beta ) = - \dfrac{b}{a} } }}[/tex]
• Sum of zeros = [tex]- \dfrac{b}{a}[/tex]
★ From 4
[tex] \sf c = k \alpha \beta - - (4)[/tex]
★ From 2 we have a = k so we have -
[tex] \sf c = a \: \alpha \: \beta[/tex]
[tex]\sf \dfrac{c}{a} = \alpha \beta[/tex]
[tex]\sf \therefore \boxed {{ \red{( \alpha \beta ) = \dfrac{c}{a} } }}[/tex]
• Product of zeros = [tex] \dfrac{c}{a}[/tex]
Also,
★ From 1
[tex]\tt \sf {a}^{2} + bx + c = k {x}^{2} -kx (\beta + \alpha)+k( \alpha \beta ) - - (1)[/tex]
[tex]\tt \sf {a}^{2} + bx + c = k \bigg( {x}^{2} -x ( \alpha + \beta ) + ( \alpha \beta \bigg) [/tex]
• Now just put S instead of sum of zeroes and P instead of product of zeroes
[tex] \tt \sf {a}^{2} + bx + c = k \bigg( {x}^{2} -x ( S ) + ( P \bigg) [/tex]
[tex]\tt \sf{a}^{2} + bx + c = \boxed{ \red{ \sf \tt k \bigg( {x}^{2} - Sx + ( P \bigg ) }}[/tex]
[tex]\rule{280pt}{2pt}[/tex]
What is the linear equation of the horizontal line that passes through the point (–3, 4)?show your work
giving brainliest!
if the ordered pair (x,y) is (-3, 4), then the othre ordered pair would (0,0)
Then, you find the slope(m).
So, m = y2 - y1
x2 - x1
if y2 is 4 and y1 is 0
x2 is -3 and y1 is 0
now you subtract to get -4
3
So, m= -4
3
Then, find the y-intercept
So, y=mx+b and substitute the ordered pair (0,0) into y= mx+b
y=mx+ b
0= -4(0) +b
3
0=0+b
-0 -0
b=0
So the equation is y= -4x
3
Which point on the number line could represent Negative 2 and one-fourth? A number line going from negative 5 to positive 5. Point A is between negative 4 and negative 3, point B is between negative 3 and negative 2, point C is between negative 2 and negative 1, point D is between negative 1 and 0. A B C Dm
Answer:
Point B
Step-by-step explanation:
Let's take your number line from -5 to +5
The point on the number line is -2 1/4
Point A is between -4 and -3, Point B is between -3 and -2, Point C is between -2 and -1, and Point D is between -1 and 0. Because -2 is not between -4 and -3 or -1 and 0, it has to be either Point B or C. Since -2 has a fraction of 1/4, it is between Point B. It would be Point C if it was -1 1/4 and not -2 1/4. Let me show you on the number line (It is not to scale, sorry haha)
<--------------------------0---------------------------->
-5 -4 -3 -2 -1 1 2 3 4 5
| | | |
A B C D
-3 > -2 1/4 > -2
Answer:
B
Step-by-step explanation:
I took the test
A circle has a circumference of 6. It has an arc of length 1.
What is the central angle of the arc, in degrees?
========================================================
Explanation:
The circumference is the perimeter of the circle. It's the distance around the circle's edge. Think of it like a fence.
The full circle's perimeter is 6 units. The arc length is a piece of that and it's 1 unit.
1/6 of the full perimeter is the arc length
1/6 of a full 360 degree rotation is (1/6)*360 = 360/6 = 60
The central angle of the arc is 60 degrees.
------------
If you want to use a formula, it would be
[tex]A = \frac{L}{C}*360[/tex]
where,
A = central angle of the arc
L = arc length
C = circumference
You would plug in L = 1 and C = 6 to find that A = 60
Bert is making a bracelet with green and blue beads. He uses green beads for the first 6
centimeters. Now, he wants to add blue beads to the bracelet so the total length is 20
centimeters. If each blue bead has a width of 7 millimeters, how many blue beads will he use
to finish the bracelet?
how to solve 2x^2+5-12=0 by factoring with detail, please!!!!!!
Answer:
[tex]x = \dfrac 32, ~ x = -4[/tex]
Step by step explanation:
[tex]~~~~~~~2x^2+5x-12=0\\\\\implies 2x^2 +8x-3x-12=0\\\\\implies 2x(x+4) -3(x+4) = 0\\\\\implies (2x-3)(x+4) = 0\\\\\implies 2x -3 = 0~~~~ \text{or}~~~~~~~~ x +4 = 0\\\\\implies 2x = 3~~~~~~~~~ \text{or}~~~~~~~~x = - 4\\\\\implies x = \dfrac 32~~~~~~~~~~ \text{or}~~~~~~~~x = - 4\\\\\text{Hence,}~ x = \dfrac 32, ~ x = -4[/tex]
The cost of 3 rackets and 2 squash balls is £26.57. The cost of 5 rackets and 7 squash balls is
The cost of 3 rackets and 2 squash balls is £26.57.
The cost of 5 rackets and 7 squash balls is £52.90.
Work out the cost of
a) a squash ball.
b) a racket
Taking into account the definition of a system of linear equations:
the cost of a squash ball and a racket are £2.35 and £7.29 respectively.the cost of 1 kg of radishes and 1 kg of carrots are £3.1 and £1.6 respectively.System of linear equationsA system of linear equations is a set of two or more equations of the first degree, in which two or more unknowns are related.
Solving a system of equations consists of finding the value of each unknown so that all the equations of the system are satisfied. That is to say, the values of the unknowns must be sought, with which when replacing, they must give the solution proposed in both equations.
Cost of a squash ball and a racketIn this case, a system of linear equations must be proposed taking into account that:
"x" represents the cost of a squash ball."y" represents the cost of a racket.The cost of 3 rackets and 2 squash balls is £26.57.
The cost of 5 rackets and 7 squash balls is £52.90.
So, the system of equations to be solved is
[tex]\left \{ {{2x+3y=26.57} \atop {7x+5y=52.90}} \right.[/tex]
There are several methods to solve a system of equations, it is decided to solve it using the substitution method, which consists of clearing one of the two variables in one of the equations of the system and substituting its value in the other equation.
In this case, isolating the variable x from the first equation:
[tex]x=\frac{26.57 - 3y}{2}[/tex]
Substituting the expression in the second you get:
[tex]7\frac{26.57 - 3y}{2}+5y=52.90[/tex]
Solving:
[tex]\frac{7}{2}(26.57 - 3y)+5y=52.90[/tex]
[tex]\frac{7}{2}x26.57 - \frac{7}{2}x3y+5y=52.90[/tex]
92.995 - 10.5y +5y= 52.90
92.995 - 5.5y= 52.90
- 5.5y= 52.90 -92.995
- 5.5y= -40.095
y= (-40.095)÷ (-5.5)
y= 7.29
So: [tex]x=\frac{26.57 - 3y}{2}=\frac{26.57 - 3x7.29}{2}[/tex]
x= 2.35
Finally, the cost of a squash ball and a racket are £2.35 and £7.29 respectively.
Cost of 1 kg of radishes and 1 kg of carrotsIn this case, a system of linear equations must be proposed taking into account that:
"x" represents the cost of 1 kg of radishes."y" represents the cost of 1 kg of carrots.The cost of 4 kg of radishes and 1.5 kg of carrots is £14.80.
The cost of 3 kg of radishes and 2 kg of carrots is £12.50.
So, the system of equations to be solved is
[tex]\left \{ {{4x+1.5y=14.80} \atop {3x+2y=12.50}} \right.[/tex]
You can solve this system using the substitution method. Isolating the variable x from the first equation:
[tex]x=\frac{14.80 - 1.5y}{4}[/tex]
Substituting the expression in the second you get:
[tex]3\frac{14.80 - 1.5y}{4}+2y=12.50[/tex]
Solving:
[tex]\frac{3}{4}(14.80 - 1.5y)+2y=12.50[/tex]
[tex]\frac{3}{4}x14.80 - \frac{3}{4}x1.5y+2y=12.50[/tex]
11.1 - 1.125y +2y= 12.50
- 1.125y +2y= 12.50 - 11.1
0.875y= 1.4
y= 1.4 ÷0.875
y=1.6
So: [tex]x=\frac{14.80 - 1.5y}{4}=\frac{14.80 - 1.5x1.6}{4}[/tex]
x= 3.1
Finally, the cost of 1 kg of radishes and 1 kg of carrots are £3.1 and £1.6 respectively.
Learn more about system of equations:
brainly.com/question/14323743
brainly.com/question/1365672
brainly.com/question/20533585
brainly.com/question/20379472
#SPJ1
(sqrt3-sqrt3i)^4
(-1+sqrt3i)^12
(sqrt 3-i)^6
(sqrt2-sqrt2i)^8
(sqrt2-i)^6Simplify the complex numbers and arrange them in increasing order of their absolute value (modulus).
The increasing order of the complex numbers is (√2 - i)⁶ < (√2 - √2i)⁸ = (√3 - i)⁶ = (-1 + √3i)¹² < (√3 - √3i)⁴.
Absolute values of the complex numbersThe absolute values of the complex numbers are determined as follows;
(sqrt3-sqrt3i)^4 = (√3 - √3i)⁴
[tex]|z| = \sqrt{(\sqrt{3} )^2 + (\sqrt{3 }\times1 )^2} } \\\\|z| = \sqrt{6}[/tex]
(-1+sqrt3i)^12 = (-1 + √3i)¹²
[tex]|z| = \sqrt{(-1)^2 + (\sqrt{3)^2} } \\\\|z| = \sqrt{4} \\\\|z| = 2[/tex]
(sqrt 3-i)^6 = (√3 - i)⁶
[tex]|z| = \sqrt{(\sqrt{3})^2 + (-1)^2 } \\\\|z| = \sqrt{4} \\\\|z| = 2[/tex]
(sqrt2-sqrt2i)^8 = (√2 - √2i)⁸
[tex]|z| = \sqrt{(\sqrt{2} )^2 + (\sqrt{2})^2 } \\\\|z| = 2[/tex]
(sqrt2-i)^6 = (√2 - i)⁶
[tex]|z| = \sqrt{(\sqrt{2})^2 + (-1)^2} } \\\\|z| = \sqrt{3}[/tex]
Increasing order of the complex numbers;
(√2 - i)⁶ < (√2 - √2i)⁸ = (√3 - i)⁶ = (-1 + √3i)¹² < (√3 - √3i)⁴.
Learn more about complex numbers here: https://brainly.com/question/10662770
#SPJ1
Answer:
see screenshot below
Step-by-step explanation:
correct on edmentum
Which graph shows a proportional relationship between x and y?
A)
B)
C)
D)
Answer:
C
Step-by-step explanation:
If the graph of a relationship is a line or a ray through the origin, then it is proportional.
The line in graph C goes through the origin (0,0)
What is the y-valye in the solution to this system of linear equations 4x+5y=-12 ; -2x+3y=-16
Answer:
4x+5y=-12
-2x+3y=-16 ×2
-----------------
eliminate x
4x+5y=-12
-4x+6y=-32
---------------+
11y=-44
y=-44/11
y=-4
y=-4 --->
-2x+3(-4)=-16
-2x-12=-16
-2x=-4
x=-4/-2
x=2
Pls Help me with this!!!
Question:
A regular triangular pyramid has a base and lateral faces that are congruent equilateral triangles. It has a lateral surface area of 81 square feet. What is the surface area of the regular triangular pyramid?
Answer:
The surface area of the regular triangular pyramid is 108 square centimetres.
Step-by-step explanation:
What is a regular triangular pyramid?
A triangular pyramid is a three-dimensional shape that has a triangular base and three triangular faces.
The lateral surface area is the area of all the sides of a 3-dimensional object excluding its base and top.
The surface area of a triangular pyramid is the sum of the areas of the four faces of the pyramid.
What is the surface area?
The area of one face = lateral surface area / 3
81 / 3 = 27
The surface area = 27 x 4 = 108
The pie below is cut into 9 equal slices. Shade 1/3 of this pie.
Answer:
shade 3 slices
Step-by-step explanation:
9*1/3=3
Solve the following inequality.
3x+5<6x-1
Answer
x > 2
Step-by-step explanation:
Isolate the variable by dividing each side by factors that dont contain the variable
Standard KY Updated Fall 2021
English
Which functions have a y-intercept that is greater than the y-intercept of the function g(x) = |x + 3] + 4? Check three
options.
2 f(x) = -2 (x - 8)2
O h(x) = -5 |xl + 10
Oj(x) = -4(× + 2)2 + 8
O K0) = }0x-412+4
O m(x) = =Ix-8| +6
[tex]f(t) = (t-s)² - q 9
(4-5)² = 9 = 0
(t - 5) ^ 2 = 9
t - 5 = 3or 4-5=-3
(x + 2)(x + 4) = 0
X+26
t=8 or t= 2
f(x) = (x + 2)(x + 4)
vertex: (5,-9) # 1rt = 5
Zeros
y = f(+)
vertex
• line of symmetry[/tex]
Using it's concept, it is found that the functions that have a greater y-intercept than g(x) = |x + 3| + 4 are given as follows:
h(x) = -5|x| + 10.k(x) = 0.25(x - 4)² + 4.m(x) = 0.25|x - 8| + 6.What is the y-intercept of a function?It is the value of the function when the input is of zero, that is, f(0). An intercept of a rational function is a point where the graph of the rational function intersects the x- or y-axis.
here, we have,
For g(x) = |x + 3| + 4, we have that g(0) = 7. As for the other functions, we have that:
f(x) = -2(x - 8)² -> f(0) = -128.
h(x) = -5|x| + 10 -> f(0) = 10 -> Greater than g(x).
j(x) = -4(x + 2)² + 8 = f(0) = -8.
k(x) = 0.25(x - 4)² + 4 -> f(0) = 8 -> Greater than g(x).
m(x) = 0.25|x - 8| + 6 -> f(0) = 8 -> Greater than g(x).
More can be learned about the y-intercept of a function at brainly.com/question/24737967
#SPJ7
Ricardo has a bag of mixed fruit snacks. In the bag, there are 12 cherry fruit snacks and 18 strawberry fruit snacks. What is the ratio of strawberry to cherry?
A.
3:2
B.
1:12
C.
2:3
Answer:
18:12 = A. 3:2
Step-by-step explanation:
Because they are equivalent ratios, they are the same, it also said ratio of strawberries to cherries so I put it in that order.
Can I please have branliest
okay thank you have a good day
Find the value of the missing angle in this triangle show work on how you found the answer.